Condylar long axis and articular eminence in MRI in patients with temporomandibular disorders. Issue 5 (2nd September 2020) - Piancino, Maria Grazia; Tepedino, Michele; Cavarra, Francesco; Bramanti, Ennio; Laganà, Giuseppina; Chimenti, Claudio; Cirillo, Stefano
ABSTRACT: Objective: To compare morphologic findings in MRI and skeletal divergence of a group of patients with temporomandibular joint disorders (TMD) subdivided into condylar symmetric and asymmetric. Methods: Fifty-nine adults (26.7 years old) with TMD were retrospectively recruited. Condylar height symmetry was evaluated by orthopantomography (Habets's method) and used to divide patients into Symmetric and Asymmetric groups; skeletal divergence was assessed on lateral cephalograms. MRI was used to evaluate the condylar long axis' angle, the glenoid fossa morphology, and the degree of disc displacement. Results: Asymmetric subjects showed a hyperdivergent skeletal pattern ( p  = 0.036), asymmetric condylar long axis ( p  = 0.018), and deeper ( p  = 0.025) and asymmetric ( p  = 0.001) glenoid fossa compared to symmetric subjects. Conclusion: Patients with TMD and condylar asymmetry diagnosed with orthopantomography are more likely to show hyperdivergent skull in cephalometry, condylar asymmetry of both height and major axis, and a steeper glenoid fossa in MRI.